Estimation of Foetal Weight by Ultrasonography and Neonate at Birth (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Ultrasonography intervention in delivery is highly sensitive and primary important for further tests of foetal well-being.Objective: The purpose of the present study was to observe the correlation of estimated foetal weight with neonatal birth weight.Methodology: This was a cross-sectional study on patients at the Labour Ward of Department of Obstetrics and Gynaecology at Sir Salimullah Medical College and Mitford Hospiptal, Dhaka, Bangladesh for six months. The women were selected who had normal pregnancy with early ultrasounographic examination for confirmation of gestational age, singleton live foetus, ultrasound examination for pregnancy profile done within 3 days before delivery. A sonographic foetal weight was estimated by using measurements of foetal body parts-biparietal diameter, abdominal circumference and femoral length. To measure the femur length, first a projection was made that shows a transverse section of one of the long bones, then scan at 900 to this to obtain a longitudinal section.Results: A total number of 100 patients were recruited for this study. The mean (±SD) sonographically estimated foetal weight was 3074±534gm with ranged from 2100 to 4100 gm. The mean (±SD) neonatal birth weight was 2978±466 gm with ranged from 2500 to 3800 gm (p